Der p 2.1 Peptide Abrogates House Dust Mites-Induced Asthma Features in Mice and Humanized Mice by Inhibiting DC-Mediated T Cell Polarization - Klein, Martin; Colas, Luc; Cheminant, Marie-Aude; Brosseau, Carole; Sauzeau, Vincent; Magnan, Antoine; Bouchaud, Grégory (Frontiers in Immunology, 2020)
Asthma is a chronic airway disease often due to sensitization to aeroallergens, especially house dust mites allergens (HDMs). The Dermatophagoides pteronyssinus group 2 (Der p 2), is one of the most representative HDM allergens and is recognized by more than 90% of HDM-allergic patients. In mouse models, all asthma-related features can be prevented by prophylactic administration of Dermatophagoides pteronyssinus 2-derived peptide (Der p 2.1). However, it is unknown whether it is able to treat well-established asthma in mice and human. We aimed here to evaluate the efficacy of Der p 2.1 immunotherapy in a mouse, humanized mouse and asthmatic patients. Asthma related-features were analyzed through airway hyperresponsiveness (AHR), allergen-specific IgE, and lung histology in mice and humanized mice. Immune profile was analyzed using lung and blood from mice and severe asthmatic patients respectively. T cell and dendritic cells (DC) polarization was evaluated using co-culture of bone marrow derived cells (BMDC) and naïve T cell from naïve mice. Mice and humanized mice both have a reduced AHR, lung tissue alteration and HDM-specific IgE under Der p 2.1 treatment. Concerning the immune profile, T helper 2 cells (Th2) and T helper 17 cells (Th17) were significantly reduced in both mice and humanized mice lung and in peripheral blood mononuclear cells (PBMC) from severe asthmatic patients after Der p 2.1 incubation. The downregulation of T cell polarization seems to be linked to an increase of IL-10-secreting DC under Der p 2.1 treatment in both mice and severe asthmatic patients. This study shows that allergen-derived peptide immunotherapy abrogates asthma-related features in mice and humanized mice by reducing Th2 and Th17 cells polarization via IL-10-secreting DC. These results suggest that Der p 2.1 peptide immunotherapy could be a promising approach to treat both Th2 and Th17 immunity in asthma.